Antecedents of Consumer Engagement in Electronic Word-Of-Mouth (EWOM) Under Consideration of Deviations Between Genders - Hoffmann, Jonas Tobias (2017)
Electronic word of mouth (eWOM) is one of the most investigated topics in contemporary marketing research and its strong impact on brand perceptions and purchase intention is making it essential for both practitioners and researchers. Several academic studies analysed the effectiveness of eWOM communication and how it influences a consumer’s purchase intention. On the contrary, few studies analysed a consumer’s antecedents to spread eWOM. This study applies the self-determination theory (SDT) from social psychology, or particularly the concept of extrinsic and altruistic motivation to explain a consumer’s eWOM intention. Indeed, some existing eWOM studies were drawing back on the SDT before, yet the novelty of this study is a broader concept of extrinsic motivation, containing the subordinate factors self-enhancement, social benefit and economic incentives. Furthermore, based on Putrevu (2001), who identified behavioural differences among genders, this study analysed these differences in an eWOM context. This study examined survey data from 223 respondents in order to analyse popular eWOM platform in consideration of age and gender and to analyse if extrinsic and altruistic motivation significantly influences one’s eWOM intention. Moreover, literature from the avenue of social psychology indicates a higher degree of altruistic behaviour for females and a stronger extrinsically orientation for males. Therefore, it has been tested if those gender differences also hold up in the eWOM context. The results of this study show significant differences in the popularity of eWOM platforms between different age groups, yet differences between genders could not be proven. Additionally, the conceptualised research model to predict a consumer’s eWOM intention yield good results, as it explains 26% of the variance. Moreover, a significantly positive influence of extrinsic motivation on eWOM intention could be evidenced.